INOVASI INSTRUMEN BIOLA BERFRET DI MTS NURHASANAH KABUPATEN BATUBARA - Fauzi, Ade; Widiastuti, Uyuni (Universitas Negeri Medan, 2020)
The purpose of this study 1) To determine the learning process of the violin using the innovation of the fret violin instrument at MTs Nurhasanah Batubara Regency, 2) To determine the process of making the violin instrument innovation. The theories used are innovation theory, learning theory, violin theory, and fret (tone barrier). Data collection techniques through observation, interviews, and documentation. The results of this study indicate 1) The learning process of the violin includes an explanation of the parts of the violin and their functions followed by reading music notation with tabulated numbers and teaching material from the Suzuki method manual. 2) The production of the stringed violin instrument consists of several stages, including: (1) the manufacturing process, (2) the manufacturing steps, (3) the materials used, and (4) the advantages and disadvantages of the stringed violin instrument. The manufacturing process is quite simple, just adding a fret that is planted on the fingerboard and then measured by a cromatic tuner measuring instrument.